Current problems of teaching chemistry at theFaculty of Pharmacy and ways to solve them - Сhulpanov K.A; Tukhtaev X.R; Jumaboev F.R; Xazratqulova S.M (Euro Asian Journal Publishing, 2025)
This article presents examples of using the Question-Answer method of the Captains' Competition method in a practical lesson on the topic of "Using interactive methods in teaching the inorganic chemistry module for pharmacy students." First of all, "Complex Compounds. The techniques for using complex questions in practical classes on the topic "Reactions of Formation of Complex Compounds" are explained
Keywords: Unique "water; like; rainbow